Caries Experience and Erosive Tooth Wear in Finnish Men Conscripts 2021: A Cross-Sectional Study - Pertti Patinen; Tarja Tanner; Mika Huttunen; Annakaisa Muhonen; Sari Räsänen; Pernelle Moilanen; Jari Päkkilä; Vuokko Anttonen; Antti Kämppi (MDPI AG, 2022)
Background: In Finland, the development of oral health in young, 19- to 21-year-old males regarding restorative treatment need seems to have slowed down according to cross-sectional conscript studies between 1976 and 2011. At the individual level, the mean number of decayed teeth (DT > 0) has also steadily continued to decline. In Finland, military service is mandatory, and around 85% of males complete it. The aim of this cross-sectional study was to investigate the oral health status of young men at the beginning of the 2020s. Methods: The data were collected in July 2021 in the eight biggest Finnish Defence force garrisons by ten calibrated dentists serving in the ranks. The inclusion criteria for this study were a year of birth between 2000 and 2002 and male gender (n = 508). Third molars were included. Restorative treatment need was evaluated using ICDAS scoring. The study was designed according to the STROBE guidelines. Results: Mean DT value was 1.13 when third molars were included and 1.03 when they were excluded. Mean DMFT value was 3.23 and 2.98, respectively. The proportion of conscripts with DT > 0 was 36.4% and 34.8%, respectively. The prevalence of caries was concentrated among a small number of conscripts. Most (76.5%) had BEWE (basic erosive wear examination) of 0-2. Conscripts in the moderate and severe ETW (erosive tooth wear) groups (BEWE 3-13) comprised 23.5% of the cohort. None of the conscripts fell into the most severe group (BEWE 14-18). Conclusions: The oral health of conscripts has improved over the last ten years, and restorative treatment need has decreased significantly. Compared to previous studies, restorative treatment need was concentrated on an even smaller proportion of conscripts.